Nioplexes encapsulated in supramolecular hybrid biohydrogels as versatile delivery platforms for nucleic acids. Issue 46 (20th April 2016) - Grijalvo, Santiago; Puras, Gustavo; Zárate, Jon; Pons, Ramon; Pedraz, Jose Luis; Eritja, Ramon; Díaz, David Díaz
Abstract : Supramolecular hydrogels based on N-protected phenylalanine (Fmoc–Phe–OH) were used to encapsulate non-ionic surfactant vesicles (niosomes). Abstract : Supramolecular hydrogels based on N-protected phenylalanine (Fmoc–Phe–OH) were used to encapsulate non-ionic surfactant vesicles (niosomes). The niosomes consisted of an amphiphilic lipid mixed with polysorbate-80 and electrostatically complexed with a fluorescently labelled oligodeoxynucleotide (FITC–ODN) as a model nucleic acid derivative. The diffusion properties of the supramolecular hydrogel were conveniently tuned by adding a small amount of κ-carrageenan (≤1% w/v) as a crosslinking agent. Interestingly, neither cationic niosomes nor the biopolymer additive significantly affected the hydrogelation properties of the amino acid-based low molecular weight (LMW) gelator. In vitro drug release experiments from Fmoc–Phe–OH hydrogels containing cationic niosomes were successfully carried out in the absence and in the presence of κ-carrageenan. The niosomal ODN liberation in solution was fitted using Higuchi, Korsmeyer–Peppas and Weibull drug release models, showing the prevalence of diffusion mechanisms in each case. Moreover, the time release was easily prolonged by increasing the concentration of κ-carrageenan. Preliminary transfection studies indicate the suitability of these supramolecular hybrid hydrogels to embed niosomal formulations and, consequently, for being used as tunable delivery vehicles for nucleic acids.